Application of project GLOBE’s cultural dimensions in evaluating ethical leadership: An intercultural study in Portugal and Guinea Bissau - Ferreira, Manuel Portugal; Mané, Mamadú Aua; Almeida, Martinho Ribeiro (Revista de Administração da UFSM, 2017)
In this article we assess how national cultural characteristics influence the perceptions of ethical leadership. Methodologically, we have conducted an empirical study relating the nine cultural dimensions of Project GLOBE – Power distance, Uncertainty avoidance, Gender egalitarianism, In-group collectivism/Institutional collectivism, Performance orientation, Future orientation, Humane orientation and Assertiveness – with ethical leadership. The sample consisted on 216 management students in Portugal (138) and Guinea Bissau (78). The analyses, using a structural model, sought to identify differences between the countries in how each of the nine cultural dimensions relates to the perception of ethical leadership behaviors. In a worldwide context where multiple concerns emerge pertaining to firms’ ethical practices, this study contributes to expand the debate on the ethical practices to the manner in which leadership is exerted. The study contributes to better understand how the cultural characteristics may promote or weaken an ethical leadership in organizations. Moreover, it focuses on two countries that are less often researched and exploring the dimension of ethical leadership that is ill understood but that may bear a substantial impact on how multinational firms organize their foreign activities.